Prevalence of diabetes and prediabetes in South Asian countries: a systematic review and meta-analysis - Masum Ali; Md Mahbub Alam; M. A. Rifat; Sonjida Mesket Simi; Sneha Sarwar; Md Ruhul Amin; Sanjib Saha (Discover Public Health)
Abstract Introduction South Asia is observing an epidemiological transition from communicable to non-communicable diseases where diabetes is an important marker. In this study, we estimate the overall prevalence of diabetes and prediabetes in South Asian countries. Method A systematic literature review and meta-analysis is performed to estimate the prevalence of diabetes and prediabetes in Bangladesh, India, Nepal, Pakistan, Sri Lanka, Bhutan, the Maldives, and Afghanistan using studies based on only the nationally representative surveys and published from 2012 until June 2024. The quality of the included articles was assessed using the Newcastle–Ottawa Scale. Both random-effect (Der Simonian-Laird inverse variance) and fixed-effect models were used to perform meta-analyses followed by meta-regression. Results We identified 64 studies for diabetes and 14 studies for prediabetes, covering a total of 4,613,487 and 156,407 participants, respectively. Overall, the pooled prevalence of diabetes and prediabetes was 8.56% (95% CI 5.73–11.91; I2 = 99.99%) and 18.99% (95% CI 12.74–26.6; I2 = 99.87%), respectively, with high heterogeneity observed among the studies based on random-effect models. We also found that the prevalence of diabetes identified by clinical methods was higher than the self-reported measures. Conclusion The analyses revealed that the prevalence of diabetes and prediabetes in South Asia throughout the study period is significantly elevated. This necessitates the establishment of comprehensive guidelines for South Asians to mitigate the escalating prevalence of diabetes and prediabetes.